(untitled) (International Journal of Engineering and Computer Science, 2018)
Mobile computing is a promising technology that is used to transmit data, voice and video through a computer or any other wireless enabled devices and there is no fixed physical link between the devices. Mobile networking is a technology that enables wireless data connection and it avoid the costly process of introducing cables. We conduct a survey based on various aspects of mobile wireless networks. The various aspects are video multicast, workload dissemination, routing and scheduling and node failures.